A Study on the Influential Factors of RMB Internationalization - Huang Yizhe (SHS Web of Conferences, 2025)
The internationalization of the RMB is a major event that changes the pattern of the world’s financial market, and the study of its influencing factors can enable RMB holders to have a clearer understanding of the process of RMB’s internationalization and the international financial situation, so that they can make correct investment judgments. This paper studies and summarizes the previous literature and finds that the influencing factors of RMB internationalization are: China’s economic strength, the degree of development financial market, the stability of the RMB’s value, the convertibility of the RMB, the political stability of China and its neighboring countries, and the inertia in the use of existing international currencies. To promote the RMB’s internationalization, China should firstly, actively promote the economic transformation to ensure the growth of economy, secondly, promote the construction of the financial market to narrow the gap with the financial markets of developed countries, thirdly, ensure the stability of RMB’s value, fourthly, promote the construction of the RMB’s freely convertible region, in addition, ensuring the political stability of itself and its neighboring countries, finally, seize the current trend of de-dollarization of the international financial market, to weaken the inertia of the use of the US dollar.